The Used of Swear Word In “Ted” (2012) Movie - Azakir Ramadhan; Murni Mahmud; Muftihaturrahmah Burhamzah (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2026)
In this study, researchers analyzed the use of swear words in the 2012 Ted film from characters in the movie. The researcher analyzes the problems, namely: (1) What What are the types of swear words that appear in the movie “Ted 2012?”, (2) What are the functions of the swear words that appear in the dialog of the movie “Ted 2012”? The movie Ted 2012 directed by MacFarlane, . This research focuses on the types and functions of swear words used by the This research focuses on the types and functions of swear words used by the film's characters, especially Ted, a teddy bear who has a funny and brash personality that significantly shapes the dialogue. This research uses a descriptive qualitative method on the sociolinguistic approach to analyze swear words in the film, This research categorizes swearing into five types: dysphemistic, idiomatic, abusively, emphatic, and cathartic, and identified five functions: abusive, humorous, expletive, euphemistic and habitual. The research found that swearing in films is used for a variety of purposes, including used for a variety of purposes, including expressing emotions, creating humor, showing tension, and strengthening interpersonal relationships. Swear words were analyzed in the characters' dialogues, which showed the relevance of swear word types and functions of swear words. In Ted's movie, swearing is often used to build the characters, drive the plot, and reflect Western cultural values. Keywords: sociolinguistic, swear word, movie, ted.